(3ebGdI GdEScfOQ GdEaQhOjSi aj GdCTjGA GdYGejI GdcdjI hCfgG djSJ HCYjGf bGFeIs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3Ef GQSWh PcQ ai cJGHg ai GdfaS (B( (3Ef GdLfS (B) (3Gdcdi EeGe Cf dGjchf TjFkG s
(3BNQgG (B:s
(3JeJ GdebGdI hGdMeO ddg cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/8) s
Keywords: (3GdadSaI hGdefWbs